Asymptomatic-anaplasmosis confirmation using genetic and serological tests and possible coinfection with spotted fever group Rickettsia: a case report - Yoo, Jiyeon (BMC Infect Dis, 2020)
BACKGROUND: Anaplasmosis is an emerging acute febrile disease that is caused by a bite of an Anaplasma phagocytophilum–infected hard tick. As for healthy patients, reports on asymptomatic anaplasmosis resulting from such tick bites are rare. CASE PRESENTATION: A 55-year-old female patient visited the hospital with a tick bite in the right infraclavicular region. The tick was suspected to have been on the patient for more than 10 days. PCR and an indirect immunofluorescence assay (IFA) were performed to identify tick-borne infectious diseases. The blood sample collected at admission yielded a positive result in nested PCR targeting Ehrlichia- or Anaplasma-specific genes groEL and ankA. Subsequent sequencing confirmed the presence of A. phagocytophilum, and seroconversion was confirmed by the IFA involving an A. phagocytophilum antigen slide. PCR detected no Rickettsia-specific genes [outer membrane protein A (ompA) or surface cell antigen 1 (sca1)], but seroconversion of spotted fever group (SFG) rickettsiosis was confirmed by an IFA. CONCLUSIONS: This study genetically and serologically confirmed an asymptomatic A. phagocytophilum infection. Although SFG rickettsiosis was not detected genetically, it was detected serologically. These findings indicate the possibility of an asymptomatic coinfection: anaplasmosis plus SFG rickettsiosis. It is, therefore, crucial for clinicians to be aware of potential asymptomatic anaplasmosis following a tick bite.